Pengaruh Firm Characteristics Dan Corporate Governance Terhadap Real Earnings Management - Jeremy Gracias Vinchen, Linda Santioso (Jurnal Paradigma Akuntansi, 2021)
This study aims to examine the effect of firm characteristics and governance on real earnings management. The dependent variable used is firm size, profitability, leverage, audit committee meetings, and board size. The independent variable is real earnings management, as measured by Roychowdhury (2006) and Al-Haddad & Whittington (2018). The research method uses multiple regression analysis. The research sample used 47 manufacturing companies listed on the Indonesia Stock Exchange for 2016-2018 which were selected using purposive sampling. The research findings show that leverage has a positive effect and other variables have no effect.